1997
DOI: 10.1007/s002800051055
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and prevention of multidrug resistance by inhibitors of P-glycoprotein

Abstract: Intrinsic and acquired multidrug resistance (MDR) in many human cancers may be due to expression of the multidrug transporter P-glycoprotein (Pgp), which is encoded by the mdr1 gene. There is substantial evidence that Pgp is expressed both as an acquired mechanism (e.g., in leukemias, lymphomas, myeloma, and breast and ovarian carcinomas) and constitutively (e.g., in colorectal and renal cancers) and that its expression is of prognostic significance in many types of cancer. Clinical trials of MDR modulation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
149
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(154 citation statements)
references
References 50 publications
1
149
0
4
Order By: Relevance
“…[18][19][20] As is well known, P-gp makes tumor cells highly resistant to a variety of anticancer drugs, and the expression of P-gp is related to the high growth activity of the tumor cells and the poor prognosis of the tumor. 16,17 The fact that P-gp expression is regulated by HIF-1a suggests that HIF-1a expression is involved in chemo-resistance of OSCC cell lines. The present study revealed that the expression levels of P-gp increased in accordance with the HIF-1a expression levels in the 4 OSCC cell lines examined, and the increase of P-gp was intimately associated with the increase of the efflux of CDDP and 5-FU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] As is well known, P-gp makes tumor cells highly resistant to a variety of anticancer drugs, and the expression of P-gp is related to the high growth activity of the tumor cells and the poor prognosis of the tumor. 16,17 The fact that P-gp expression is regulated by HIF-1a suggests that HIF-1a expression is involved in chemo-resistance of OSCC cell lines. The present study revealed that the expression levels of P-gp increased in accordance with the HIF-1a expression levels in the 4 OSCC cell lines examined, and the increase of P-gp was intimately associated with the increase of the efflux of CDDP and 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 MDR1 gene expression with subsequent functional P-gp expression is markedly upregulated in a HIF-1-dependent manner in response to hypoxia. 18,19 Hypoxia-elicited MDR1 expression resulting from HIF-1 activation depends at least in part on signaling via activation of JNK.…”
mentioning
confidence: 97%
“…Very few studies have addressed the approach of resistance prevention, most being concerned with resistance reversal. Sikic et al (1997) have shown that the MDR modulator PSC 833 can decrease the mutation rate for resistance to doxorubicin by suppressing the activation of the MDR1 gene and the appearance of MDR mutants. Our findings of reduced MDR1 expression in sublines grown in the presence of both doxorubicin and dexrazoxane support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Efflux transporter molecules, particularly P-gp, alter the plasma concentration of the drugs by pumping them back into the intestinal lumen [1]. However, the function of P-gp may be affected by some modulating or inhibiting agents [10]. Verapamil, which increased the intestinal absorption of cyclosporine and tacrolimus in this study, has previously been reported to be a substrate of P-gp when used in low doses and to strongly inhibit P-gp when used high doses [8].…”
Section: Discussionmentioning
confidence: 99%